Development and results of the German National Strategy for the Promotion of Breastfeeding: a participatory process - Brettschneider, Anna-Kristin; Steindl, Jana; Matthes-Bolz, Beate; Lehmann, Iris; Hilger-Kolb, Jennifer; Roskosch, Elena; Strauß, Gabriele; Hoffmann, Mariell; Ensenauer, Regina (Frontiers in Public Health, 2025)
Breast milk is the optimal nutrition for infants. However, the proportion of mothers who exclusively breastfeed their children in Germany is low (40% end of 4th month; 13% end of 6th month). A systematic evaluation of breastfeeding promotion has ranked Germany as moderately breastfeeding-friendly. Therefore, the federal government has commissioned the Department of Child Nutrition at the Max Rubner-Institut to coordinate the interdisciplinary development and implementation of a German National Strategy for the Promotion of Breastfeeding. In a participatory process, over 150 stakeholders have conceptualized measures to promote breastfeeding in seven strategic fields: (1) “Evidence-based guidelines,” (2) “Basic/advanced training and continued professional development,” (3) “Prevention and healthcare structures,” (4) “Breastfeeding promotion by municipalities,” (5) “Breastfeeding in the workplace,” (6) “Marketing of breast-milk substitutes,” and (7) “Systematic breastfeeding monitoring.” Measures include e.g., the development of an evidence-based medical guideline for breastfeeding duration and interventions to promote breastfeeding as a basis for education and training for involved occupational groups. Another measure is to establish a new research field at the Department of Child Nutrition to develop a systematic breastfeeding monitoring system. Additional measures concern the development of more breastfeeding-friendly framework conditions in healthcare structures, municipalities, and in the workplace, as well as regulations for the marketing of breast-milk substitutes and the development of communication strategies to promote breastfeeding. Following the adoption by the Federal Cabinet, the strategy serves as the basis for a sustainable improvement of breastfeeding promotion in Germany.